Macroscopic and Microscopic Gradient Structures of Bamboo Culms - Suwat SUTNAUN; Siripong SRISUWAN; Patcharin JINDASAI; Banyat CHERDCHIM; Nirundorn MATAN; Buhnnum KYOKONG (Walailak Journal of Science and Technology, 2011)
This work studied the structure of bamboo culms which is naturally designed to retard the bending stress caused by a wind load. A macroscopic gradient structure (diameter, thickness and internodal length) and a microscopic one (distribution of fiber) of three sympodial bamboo species i.e. Tong bamboo (Dendrocalamus asper Backer.), Pah bamboo (Gigantochloa bambos) and Pak bamboo (Gigantochloa hasskarliana) were examined. From the macroscopic point of view, the wind-load generated bending stress for the tapered hollow tube of bamboo was found to vary uniformly with height, especially at the middle of the culms. Furthermore, the macroscopic shape of bamboo culm is about 2-6 times stiffer in bending mode than one with a solid circular section for the same amount of wood material. Microscopically, the distribution of fiber in the radial direction linearly decreases from the outer surface to the inner surface in the same manner as that of the distribution of the bending stress in the radial direction. Distribution of fiber along the vertical length of bamboos at each height is proportional to the level of bending stress generated by the wind load. Both macroscopic and microscopic gradient structures of sympodial type bamboos were found to be less effective to retard the bending stress than those of monopodial type bamboo.